Studi Penerapan Terapi Musik Klasik Mozart Terhadap Penurunan Tingkat Halusinasi Pendengaran pada Pasien Gangguan Jiwa di Panti Sosial - Niken Ayu Setyowati; Yunita Astriani Hardayani (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Hallucinations are a major clinical manifestation of schizophrenia, with auditory hallucinations being the most prevalent type that severely impacts a patient's cognitive and social functioning. Non-pharmacological interventions, such as listening to classical music, are required to complement medical treatment and induce physiological relaxation. Methods: This study used a descriptive case study approach with four schizophrenic patients presenting auditory hallucinations at the Panti Sosial Bina Laras Harapan Sentosa. The intervention consisted of listening to Mozart's classical music for 15–30 minutes per session, administered daily over 6 consecutive days. Data collection included observations and structured interviews using a 22-item hallucination symptom checklist developed by the Universitas Indonesia. Results: The baseline pre-test indicated significant hallucination severity across all respondents. Post-intervention measurements showed a prominent reduction in hallucination symptoms: Respondent 1 and Respondent 3 achieved a 45.4% symptom decrease, Respondent 2 showed a 40.9% decrease, and Respondent 4 experienced a 27.3% decrease. Behaviors such as self-talking, unprovoked laughter, and panic attacks were substantially minimized. Conclusion: The systematic application of Mozart's classical music therapy effectively mitigates the signs and symptoms of auditory hallucinations by stimulating relaxation and diverting internal psychotic stimuli.